Relationship between helicobacter pylori infection and nonsteroidal anti-inflammatory drug-induced gastroduodenal mucosal injury - Sait BAĞCI,; Haşim ÇAKIRBAY,; Murat DEMİRİZ,; Mustafa GÜLŞEN,; Mehmet KARALAR,; Oktay ARPACIOĞLU,; Ahmet ALPER, (Turkish Journal of Gastroenterology, 2020)
-